2021
DOI: 10.24843/jbeta.2022.v10.i01.p11
|View full text |Cite
|
Sign up to set email alerts
|

Memperpanjang Masa Kesegaran Bunga Potong Gerbera (Gerbera jamesonii) Dengan Pemanfaatan Gula dan Cuka Dapur (Asam Asetat) Sebagai Larutan Peraga (Teknik Holding)

Abstract: ABSTRAK Penelitian ini bertujuan untuk mendapatkan konsentrasi terbaik gula dan cuka dapur (asam asetat) 25% sebagai larutan peraga untuk memperpanjang masa kesegaran bunga potong Gerbera (Gerbera Jamesonii). Penelitian ini di lakukan di Laboraturium Pascapanen Fakultas Teknnologi Pertanian Gedung Agrokomplek Universitas Udayana Sudirman Denpasar. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan dua faktor perlakuan yaitu gula dengan konsentrasi (0%, 2%, 4%, 6%, 8%) dan faktor cuka d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The public also demands H. annuus, C. chinensis and G. jamesonii as ornamental plants and cut flowers as flower bouquets and wedding decorations [29,30]. Research has shown that a combination of 25% sugar and acetic acid significantly affects the freshness of flowers G. jamensonii [31]. The other species, T. erecta, found at all observation locations prove this plant is popular with the community.…”
Section: Resultsmentioning
confidence: 98%
“…The public also demands H. annuus, C. chinensis and G. jamesonii as ornamental plants and cut flowers as flower bouquets and wedding decorations [29,30]. Research has shown that a combination of 25% sugar and acetic acid significantly affects the freshness of flowers G. jamensonii [31]. The other species, T. erecta, found at all observation locations prove this plant is popular with the community.…”
Section: Resultsmentioning
confidence: 98%